Optimalisasi Pemanfaatan Bonggol Jagung di Dusun Ngantru Desa Sekaran Kecamatan Kasiman Kabupaten Bojonegoro - Ernanti, Deya; Cahyono, Edi Dwi; Susilo, Edi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to understand farmers' habits in managing corn cob waste in Dusun Ngantru, Sekaran Village, Kasiman District, and to formulate strategies to optimize waste management. The main issue addressed is the suboptimal utilization of corn cob waste, despite its significant economic potential. Through a qualitative descriptive method employing snowball sampling technique, this study identifies farmers' habits, optimization strategies, and the impacts of corn cob waste management. The findings reveal that farmers' habits in managing corn waste are influenced by local traditions and knowledge. Optimizing the utilization of corn cob waste can lead to significant economic and environmental impacts, including increased income, reduction of organic waste, and enhanced environmental awareness. Optimization strategies include training, cross-sector collaboration, creative marketing approaches, and environmental awareness campaigns.